Prevalence and factors associated with the use of psychotropics in the elderly: an integrative review (Research, Society and Development, 2021)
Objective: To describe the difficulties and strategies faced in the use of controlled medications among the elderly through an investigation in the available scientific literature. Methodology: This is an integrative literature review. We used scientific productions based on the following journals: Scopus, Web of Science and PubMed. Inclusion criteria included original articles published between 2016 and 2021, in Portuguese and English, and that addressed the theme studied. Using the Boolean operator "AND" together with the descriptors: Elderly; Psychotropic drugs; Prevalence. Results: The main difficulties and strategies found in the present study was similar to several studies that report the relationship between the use of psychotropic medications, where the great demand is associated with depression and low quality of life, corroborating with the understanding about the types of psychotropic medications, duration of treatment, and to associated factors that end up leading to consumption. Conclusion: It is necessary that there is a restructuring of health services in order to offer elderly patients greater safety in the therapeutic conduct applied, in order to minimize adverse side effects, guiding on the correct use of medications according to their needs, through specialized professionals and trained prescribers.